2020
DOI: 10.1111/asj.13366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fecal microbiota of two monogastric herbivorous and five omnivorous mammals

Abstract: The intestine harbors a dense, delicately balanced microbial population that mainly consists of bacteria (O'Hara & Shanahan, 2006). In general, the gut microbiota plays three major roles in the host's physiology: breaks down and utilizes dietary fiber that otherwise the host would not be able to, such as resistant polysaccharide; prevents adherence of pathogenic bacteria by competing for ecological niches and nutritional components; and synthesizes certain compounds such as vitamins, serotonin, and dopamine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…The comparison of faecal bacterial composition in this study indicated that intestinal bacterial flora in conventional marmosets is similar to that in humans, such as Bifidobacterium colonisation, which did not occur in SPF mice. Spontaneous Bifidobacterium colonisation was also consistently observed in marmosets from other facilities 30,31 . Furthermore, the inoculation of the intestinal bacterial strains obtained from humans showed that marmosets underwent significantly steady colonisation by all these strains, suggesting similar colonisation milieu for intestinal bacteria with humans.…”
Section: Discussionmentioning
confidence: 59%
“…The comparison of faecal bacterial composition in this study indicated that intestinal bacterial flora in conventional marmosets is similar to that in humans, such as Bifidobacterium colonisation, which did not occur in SPF mice. Spontaneous Bifidobacterium colonisation was also consistently observed in marmosets from other facilities 30,31 . Furthermore, the inoculation of the intestinal bacterial strains obtained from humans showed that marmosets underwent significantly steady colonisation by all these strains, suggesting similar colonisation milieu for intestinal bacteria with humans.…”
Section: Discussionmentioning
confidence: 59%
“…Horses and humans have distinctly different gastrointestinal tract anatomy and physiology. Humans are monogastric omnivores, whereas horses are monogastric hindgut fermenting herbivores with a specialized large cecum and colon utilized for bacterial breakdown and utilization of fiber [ 37 , 38 , 39 ]. These anatomic and dietary differences are reflected in the unique fecal microbiota profiles found in the two species.…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing the fecal microbiota of several different herbivorous and omnivorous mammals, the fecal microbiota of horses had significantly higher alpha diversity with a higher abundance of cellulolytic bacteria than humans. Additionally, on beta diversity analysis in the PCoA plot, horses and other herbivores clustered separately from humans [ 37 ]. These findings may account for the differences in results seen between the present study and the available literature characterizing the fecal microbiota in humans with autoimmune uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…Most bacteria observed were acetate-or propionate-producers, such as Bacteroides, Prevotella, Anaerobiospirillum, Phascolarctobacterium, Megamonas, and Megasphaera, with a low abundance of butyrate producers, such as Lachnospiraceae 43 . However, Megasphaera has been known to produce butyrate under specific conditions 33,44 . Inter-institutional differences greatly affect marmoset microbiomes, as previous studies report marmoset gut microbiota dominated by Actinobacteria 29,30 , Firmicutes 33,34 , Proteobacteria 24,45,46 and Bacteroidetes 31,32,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Marmosets are exudivores that consume large amounts of indigestible oligosaccharides from tree gums 28 , and may harbor specific gut microbes dedicated to carbohydrate metabolism. Currently, few reports on the marmoset microbiome are available [29][30][31][32][33][34] . In this study, we evaluated microbiome, serum chemistry and complete blood count (CBC) samples from healthy marmosets (n=91) and marmosets with IBD (n=59) or duodenal ulcer/strictures (n=23), collected during physical examinations or necropsies over a two-year period.…”
Section: Introductionmentioning
confidence: 99%